2022
DOI: 10.47665/tb.39.3.006
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis in captivated and free-ranging wild animals worldwide: a review

Abstract: Blastocystis is the most prevalent eukaryotic gastrointestinal symbiont found in humans and animals worldwide. Increased human infection rates are associated with raising concerns about the involvement of the parasite in public health. Over the last decade, the number of linked epidemiology studies has been prudently grown. Microscopy has been used to detect the presence of protozoan and the advent of molecular techniques has made detection easier. However, due to its limited host specificity and zoonotic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In the past, ST6 was seen among chicken slaughterhouse workers in Lebanon [ 88 ], and ST5 was seen among pig handlers in Thailand [ 89 ]. Other subtypes, such as ST7–ST14, were also frequently found in domestic animals and wild animals in prior studies conducted in Malaysia and elsewhere [ 90 , 91 ] but were not observed in humans in our systematic review. The presence of ST5 and ST6 among various cohorts in Malaysia indicates zoonotic transmission, as these subtypes have been reported among the domestic animals [ 92 ].…”
Section: Discussionsupporting
confidence: 51%
“…In the past, ST6 was seen among chicken slaughterhouse workers in Lebanon [ 88 ], and ST5 was seen among pig handlers in Thailand [ 89 ]. Other subtypes, such as ST7–ST14, were also frequently found in domestic animals and wild animals in prior studies conducted in Malaysia and elsewhere [ 90 , 91 ] but were not observed in humans in our systematic review. The presence of ST5 and ST6 among various cohorts in Malaysia indicates zoonotic transmission, as these subtypes have been reported among the domestic animals [ 92 ].…”
Section: Discussionsupporting
confidence: 51%
“…By grouping the bovine ST10 and ST14 isolates, persons living in the Quang Nam area had a 3.4 higher risk of infection by these isolates, compared to persons from Da Nang (OR: 3.400, CI: 1.302–10.583, p = 0.019). This difference in ST distribution could be explained by the rurality of the province of Quang Nam in comparison to the more urbanized Da Nang area and the increased presence in the vicinity of dwellings of poultry and livestock, which are known to be carriers of ST7 and ST10/ST14 [ 8 , 9 , 10 ], respectively, and thus potential reservoirs of parasite transmission to inhabitants. Moreover, individuals who drank well water (OR: 10.875, CI: 1.770–68.146, p = 0.008) or presented constipation (OR: 11.375, CI: 1.311–81.393, p = 0.016) were significantly predictive of the risk of ST1 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the distribution of STs in Vietnam presented a major particularity, with a large proportion of isolates considered as zoonotic. Indeed, the avian ST6 and ST7, the ST8 known to colonize primates as other hosts, and the bovine-adapted ST10 and ST14 [ 2 , 8 , 9 , 10 , 35 ] accounted for more than 50% of the subtyped isolates, highlighting a wide zoonotic transmission of Blastocystis sp. in this Vietnamese cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations